Burst fracture of the thoracolumbar spine: correlation between kyphosis and clinical result of the treatment - Rodrigo Arnold Tisot; Juliano da Silveira Vieira; Renato Tadeu dos Santos; Augusto Alves Badotti; Diego da Silva Collares; Leonardo Domingues Stumm; Bruno Brum Barreto; Paulo Bruno Camargo (Coluna/Columna, 2015)
OBJECTIVE: To evaluate the correlation between kyphosis due to burst fractures of thoracic and lumbar spine and clinical outcome in patients undergoing conservative or surgical treatment. METHODS: A retrospective, cross-sectional study was conducted with 29 patients with thoracolumbar burst fractures treated by the Spine Group in a trauma reference hospital between the years 2002 and 2011. Patients were followed-up as outpatients for a minimum of 24 months. All cases were clinically evaluated by Oswestry and SF-36 quality of life questionnaires and the visual analogue scale (VAS) of pain. They were also evaluated by X-ray examinations and CT scans of the lumbosacral spine at the time of hospitalization and subsequently as outpatients by Cobb method for measuring the degree of kyphosis. RESULTS: There was no statistically significant correlation between the degree of initial kyphosis and clinical outcome measured by VAS and by most of the SF-36 domains in both patients treated conservatively and the surgically treated. The Oswestry questionnaire showed benefits for patients who received conservative treatment (p=0.047) compared to those surgically treated (p=0.335). The analysis of difference between initial and final kyphosis and final kyphosis alone in relation to clinical outcome showed no statistical correlation in any of the scores used. CONCLUSION: The clinical outcome of treatment of the thoracic and lumbar burst fractures was not influenced by a greater or lesser degree of initial or residual kyphosis, regardless of the type of treatment.